Prevalence of and factors associated with sarcopenia in patients on hemodialysis in Brazil: findings from the multicenter SARC-HD study - Duarte, Marvery P.; Nóbrega, Otávio T.; Vogt, Barbara P.; Pereira, Marina S.; Vieira, Fábio A.; Silva, Maryanne Z. C.; Disessa, Henrique S.; Mondini, Dario R.; Krug, Rodrigo R.; Sant’Helena, Bruna M.; Bundchen, Daiana C.; Bohlke, Maristela; et al. (Frontiers in Medicine, 2026)
ObjectiveThe understanding of sarcopenia in patients on hemodialysis from middle-income countries remains underexplored. We investigated the prevalence of and factors associated with sarcopenia in patients undergoing hemodialysis in Brazil.MethodsThis was a cross-sectional analysis using baseline data from the SARCopenia trajectories and associations with clinical outcomes in patients on HemoDialysis (SARC-HD) multicenter study. Muscle strength was assessed by handgrip, muscle mass by calf circumference, and physical performance by the 4-m gait speed test. Sarcopenia was diagnosed and staged as probable, confirmed, or severe based on the revised European Working Group on Sarcopenia in Older People (EWGSOP2) consensus. Associated factors were investigated with adjustment for potential confounders.ResultsA total of 983 patients (median age 59 years; 48% ≥ 60 years; 40% female) from 19 dialysis centers were analyzed. The prevalences of probable, confirmed, and severe sarcopenia were 12, 9, and 5%, respectively. Sarcopenia prevalence increased with age, ranging from 7 to 45% in the male individuals and from 4 to 21% in the female individuals. In the fully adjusted model, older age [≥60 years; adjusted odds ratio (aOR): 3.30, 95% confidence interval (CI): 2.09–5.21], male sex (aOR: 1.77, 95% CI: 1.13–2.77), white ethnicity (aOR: 1.88, 95% CI: 1.23–2.87), and diabetes as the etiology/comorbidity of chronic kidney disease (CKD) (aOR: 1.83, 95% CI: 1.20–2.91) were independently associated with higher odds of sarcopenia. Nevertheless, overweight (aOR: 0.38, 95% CI: 0.24–0.60) and obesity (aOR: 0.11, 95% CI: 0.05–0.26) were associated with lower odds. After sensitivity analyses based on dialysis prescription, only older age, white ethnicity, overweight, and obesity remained independently associated with sarcopenia.ConclusionOne in four patients on hemodialysis had some stage of sarcopenia. Independent risk factors associated with sarcopenia were older age and white ethnicity, whereas overweight and obesity were protective factors. These findings may help identify hemodialysis patients at increased risk of sarcopenia, thereby promoting early screening, diagnosis, and treatment strategies.